CHILDFREE PERSPEKTIF HAK ASASI MANUSIA DAN MAQASID SYARI’AH JAMALUDDIN ‘ATHIYYAH (Ahkam: Jurnal Hukum Islam, 2023)
This article examines the phenomenon of childfree from the perspectives of human rights (HR) and Maqasid Shariah. Childfree refers to the decision made by individuals or couples to remain without children, despite having the ability to conceive. This phenomenon remains controversial in society, as it is seen as contradicting human nature, religion, and cultural values. However, within the framework of human rights, every individual has the right to make decisions regarding their own reproduction, including the choice to not have children. This article analyzes the religious viewpoints, particularly in Islam, on childfree and aligns them with the principles of human rights that recognize individual equality and freedom. Additionally, the Maqasid Shariah perspective of Jamaluddin 'Athiyyah is employed to explore the sustainability of offspring as a protected right. Through a normative approach, this article discusses the implications of childfree in the contexts of human rights and Maqasid Shariah and argues that childfree individuals should be treated fairly and equally without discrimination. This research utilizes a literature review method, collecting qualitative data from relevant secondary sources. The findings and discussions of this article aim to provide a deeper understanding of the childfree phenomenon from the perspectives of human rights and Maqasid Shariah, as well as contribute to advocating for the recognition of individual rights in making decisions about their own reproduction.